PENEGAKAN HUKUM TERHADAP PENJUALAN BBM MENGGUNAKAN NAMA PERTAMINI SECARA ILEGAL DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 22 TAHUN 2001 TENTANG MINYAK DAN GAS BUMI - Edo Bikana Barus; Erdianto Erdianto; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Oil and natural gas are one of the largest natural resources owned by Indonesia. Indonesian mining produces oil and natural gas, which are strategic natural resources that are not renewable and are vital commodity assets that control the lives of many people. This commodity also has an important role in the national economy so that its management must be able to optimally provide the welfare and prosperity of the people.This type of research can be classified in the type of sociological legal research (empirical), because in this study the author directly conducted research at the location or place being studied in order to provide a complete and clear picture of the problem under study. This research was conducted at the Pekanbaru City Police, while the population and sample were the Head of Criminal Investigation Unit of the Pekanbaru Police (Economic Section), Investigators (Economic Section), and the perpetrators of illegal petrol sales using the name Pertamini. The data sources used are primary data and secondary data.The conclusions that can be obtained from the research results are: First, the implementation of law enforcement against oil fuel sales actors who use the first name illegally which is currently carried out is still not in accordance with their authority and is less effective in implementing both administrative and criminal sanctions. Second, the obstacle in law enforcement against oil fuel sales actors who use the first name illegally is that a law enforcer must carry out a legal process when he finds out that a law violation has been committe. However, the police cannot just enforce the law against retailers using the Pertamini brand because there are reasons that make it easier for the community. Third, efforts that can be made to overcome the obstacles to law enforcement against oil fuel sales actors who use the first name illegally are to raise legal awareness for the public by conducting direct socialization to retail sellers that there are regulations regarding the sale of oil and so that the public knows what is allowed.Keywords: Fuel Oil, Illegal, Oil and Gas, First, Crime.